Forensic psychiatry and ethical approaches in legal issues - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
Forensic Psychiatry is a field that is more specialized in psychiatry. Specialists who are working in this field are confronted with many ethical-legal problems. Although forensic psychiatry field has multidisciplinary interactions, in literature, there are limited publications about forensic psychiatry. In this book, authors who are experts in their fields, state the main problems confronted by forensic psychiatrists and put forth ethical approaches for legal and ethical problems. The authors emphasize the basic clinical skills and the trainee of the expert is required for a full assessment and understanding of any forensic psychiatry issue. The text also emphasizes an evidence-based approach to practice and gives full attention to ethical and legal issues. This book integrates the classical principles of medical ethics with modern medical applications while demonstrating the clinical applications of this knowledge for the diagnosis and management of a wide range of forensic psychiatry topics. This book will be useful for qualified psychiatrists, forensic medicine specialists, medical students, and those in fields related to current forensic psychiatry practices. © 2021 by Nova Science Publishers, Inc. All rights reserved.